Effects of supplementation with β‐carotene on the growth performance and intestinal mucosal barriers in layer‐type cockerels. (4th March 2020) - Hui, Junnan; Li, Lingxi; Li, Ruonan; Wu, Min; Yang, Yu; Wang, Jinghui; Fan, Yuanyuan; Zheng, Xin
Abstract: β‐carotene is a robust modulator of mucosal barriers, and it can amplify the immunoglobulin A (IgA) response via the retinoic acid (RA)–mediated pathway. We investigated the influence of β‐carotene on intestinal barriers in layer‐type cockerels. In this study, β‐carotene has a positive influence on growth performance and intestinal morphology. β‐carotene remarkably enhanced serum secretory immunoglobulin A (sIgA) levels, jejunal mucosal sIgA, and IgA concentrations. β‐Carotene significantly enhanced mRNA expression levels of IgA, CC chemokine receptor‐9 (CCR9), polymeric immunoglobulin receptor (pIgR), and retinoic acid receptor α (RARα) in the ileal tissues and pIgR in the jejunal tissues. β‐Carotene improves mRNA expression of intestinal barrier‐related proteins including: mucin‐2 (MUC‐2), zonula occludens‐2 (ZO‐2), occludins (OCLN), and zonula occludens‐1 (ZO‐1) in the ileal tissues. Moreover, β‐carotene decreased the levels of Escherichia coli and elevates the levels of Lactobacillus. The results indicate that β‐carotene can promote growth performance and contribute to the gradual development of intestinal barriers in Hyline Brown chicks. This study enriches our knowledge about the effects of β‐carotene on intestinal barrier and highlights a theoretical basis of β‐carotene application in the poultry industry.